2017
DOI: 10.1038/srep41235
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin: full-length protein and one of its chains show opposing effects on cellular lipid accumulation

Abstract: Proteins, made up of either single or multiple chains, are designed to carry out specific biological functions. We found an interesting example of a two-chain protein where administration of one of its chains leads to a diametrically opposite outcome than that reported for the full-length protein. Clusterin is a highly glycosylated protein consisting of two chains, α- and β-clusterin. We have investigated the conformational features, cellular localization, lipid accumulation, in vivo effects and histological c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…In the present study, we found that Clu regulated myogenic marker genes during the differentiation stage in C2C12 cells. To examine its effect on lipid accumulation, we analyzed the expression of CD36 and PPARγ (well‐known lipid markers) and observed their diminished expression in Clu kd cells, which is in line with the lipid accumulating effect of Clu reported by Matukumalli et al (47). We examined lipid accumulation in FMOD wt and FMOD kd cells.…”
Section: Discussionsupporting
confidence: 78%
“…In the present study, we found that Clu regulated myogenic marker genes during the differentiation stage in C2C12 cells. To examine its effect on lipid accumulation, we analyzed the expression of CD36 and PPARγ (well‐known lipid markers) and observed their diminished expression in Clu kd cells, which is in line with the lipid accumulating effect of Clu reported by Matukumalli et al (47). We examined lipid accumulation in FMOD wt and FMOD kd cells.…”
Section: Discussionsupporting
confidence: 78%
“…Matukumalli, Tangirala, and Rao (2017) proved that the properties of CLU differed depending on its subcellular localization. The authors documented that CLU composed of both (α and β) subunits lowered the lipid levels, whereas β‐chains caused intracellular lipid accumulation two times higher in comparison to the controls.…”
Section: Clu Structure and Function In The Male Reproductive Tractmentioning
confidence: 99%
“…The α‐subunit did not present those features. Moreover, the weight of rabbits treated with β‐chains of CLU increased by 40% compared to the control, despite no change in the eating habits (Matukumalli et al, 2017).…”
Section: Clu Structure and Function In The Male Reproductive Tractmentioning
confidence: 99%
“…Clusterin, a stress-induced chaperon protein (71), is involved in cell signaling (72), apoptosis (73), cellular migration (74), metastasis (75), DNA repair (76,77), lipid accumulation (78), and lipid transport (79). Clusterin was selected as a candidate to study further as it ranked as one of the top regulated candidates of E6AP and some of its functions are related to the biology of E6AP.…”
Section: Discussionmentioning
confidence: 99%